Impact of preoperative percutaneous transhepatic biliary drainage on post‐operative survival in patients with distal cholangiocarcinoma. Issue 9 (7th July 2019) - Mori, Shozo; Aoki, Taku; Park, Kyung‐Hwa; Shiraki, Takayuki; Sakuraoka, Yuki; Iso, Yukihiro; Kato, Masato; Kubota, Keiichi
Abstract : Background: The aim of this study was to investigate the long‐term impact of the type of preoperative biliary drainage used for patients undergoing pancreatoduodenectomy for distal cholangiocarcinoma (DCC). Methods: A total of 84 patients with DCC who underwent preoperative biliary drainage between June 2000 and December 2016 were divided into groups for whom percutaneous transhepatic biliary drainage (PTBD) ( n = 24) or endoscopic biliary drainage (EBD) ( n = 60) was used. Results: The 5‐year overall survival in the PTBD group was significantly worse than that in the EBD group (16.7% versus 52.3%, P = 0.007). After propensity score matching (22 patients in each group), the 5‐year overall survival in the PTBD group was still worse than that in the EBD group (13.6% versus 61.2%, P = 0.003). Multivariate analysis revealed that PTBD was independent risk factor for both poor survival ( P = 0.028) and peritoneal recurrence ( P = 0.018). The incidence of multiple sites at initial recurrence tended to be higher in the PTBD group than in the EBD group ( P = 0.080). Conclusions: PTBD should not be performed for patients undergoing pancreatoduodenectomy for DCC, except when EBD is contraindicated, as PTBD is significantly associated with shorter survival and peritoneal recurrence.